The difficult transition to modernity: the press in Colombia - Cubillos Vergara, María Carolina (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
This article shows a retrospective view, which attempts to recognize in the past, the evidences that show the press as a product of modernity, resulted from ideological and material changes experienced in the Colombian society between the late eighteenth and mid-twentieth century. For this reason, its theoretical basis is founded on the ideas of Roger Chartier, who, from the field of cultural history, defines text as a result of a process which combines writing and material forms at its birth and diffusion, in a specific period. This suggest validating the idea of written text as a cultural and social reference, resulted of a collective process similar to the a mechanism that materialize it, and which simultaneously combine variations in spelling, layouts, forms of ownership (uses and decodes of the readers/listeners) to the legal, religious, aesthetic and commercial devices that redefine its content in order to adapt to the ideological and mental trends present in a particular era.